A new air handling unit system for residential buildings: experiment and simulation-based analysis. Issue 5 (September 2019) - Lazzarini, Emanuele; Zarrella, Angelo; Emmi, Giuseppe; Biasin, Enrico
Abstract: Energy saving in buildings is one of the main priorities of the last years. To reach this goal, the optimization of the building envelope and plant-systems with high energy performance are necessary. This work looks at the use of the air-handling unit based systems for heating and cooling of residential dwellings characterized by high thermal insulation level. A plant system based on a new concept of air-handling unit is analyzed by means of experimental analysis carried out in a real common apartment, named DemoLab and realised near Padova (Italy). This system provides both the heating and cooling thermal loads. The research outlines the analysis of the test measurements carried out in the laboratory, focusing on the profiles of air temperature, humidity and CO2 rate in several points and different rooms. As result, the analysis verified the control strategy implemented in the investigated plant system to improve the indoor environmental quality inside the building. Finally, the new system was also analysed in different climatic conditions by means of transient computer simulations implementing the current control strategies.